0611 Intraindividual Variability in Subjective Sleep and Average Fatigue in Parents of Children on the Autism Spectrum. (25th May 2022) - Hayse, Braden; Stearns, Melanie; Mazurek, Micah; Curtis, Ashley; Nair, Neetu; Beversdorf, David; Golzy, Mojgan; Sohl, Kristin; Ner, Zarah; Davis, Beth; Takahashi, Nicole; McCrae, Christina
Abstract: Introduction: Fatigue is related to various adverse health outcomes. Mean levels of some common sleep variables, such as total sleep time (TST), sleep onset latency (SOL), and wake after sleep onset (WASO), have been associated with fatigue. However, intraindividual variability (IIV) of sleep parameters might play an independent role in sleep's relationship with fatigue. Understanding fatigue is particularly important for parents of children with autism spectrum disorder (ASD) given fatigue's negative associations with positive parenting and implementation of child interventions. This preliminary study examined linear associations between subjective sleep IIV and mean fatigue levels in parents of children on the autism spectrum. Methods: The sample included 66 parents who expressed interest in a behavioral treatment sleep study for their school-aged children diagnosed with ASD (6-12 years old; NCT04545606). All parents (Mage=37.03, SD=6.53; 91% female) completed daily electronic diaries over a two-week baseline period. Daily fatigue rating was collected using a visual analog scale (0-100) and averaged within individuals. Within-individual standard deviations of subjective TST, SOL, and WASO were calculated to estimate IIV. Data were analyzed in R (v4.1.2) using multiple linear regression models controlling for participant age, gender, and individual sleep parameter means. Results: Bivariate correlations between sleep variable IIV and average fatigue indicated a positive association between TST variability and average fatigue, r(64)=0.33, p<0.01. Multiple regression analyses showed that greater IIV of TST was associated with higher average fatigue (β=0.14, 95%CI [0.01, 0.27], sr2=0.06, p=0.041). No significant associations were found between average fatigue level and IIV of WASO or SOL. Conclusion: Results suggest that greater TST variability may be one factor independently contributing to higher fatigue levels in parents of children on the autism spectrum, which warrants further examination of sleep variability in this population. Future research could explore IIV of additional sleep parameters, fatigue IIV as an outcome, alternative methods of sleep measurement, and study designs that address causation. Increased insight into these connections might inform the importance of considering sleep interventions for both children and parents, and potential subsequent treatment benefits. Support (If Any): MU Research Board Grant (McCrae, PI); Department of Defense Autism Research Program (McCrae, PI; W81XWH2010399).